2011
DOI: 10.1016/j.etp.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and apoptosis in an animal model of reversible renal injury

Abstract: High adenine phosphate (HAP) diet serves as an animal model of chronic renal failure (RF). Induction of RF and establishment of end organ damage require long exposure periods to this diet. Previously, we have shown that RF is reversible after diet cessation even after protracted administration. In this study, we explored the underlying renal changes and cellular pathways occurring during administration and after cessation of the diet. Kidneys were obtained from rats fed HAP diet for 7 weeks, and from rats fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
(14 reference statements)
3
24
0
1
Order By: Relevance
“…In another report, it has been shown that, in an adenine-loaded rat, which is widely used as a model for renal failure, cessation of the adenine diet led to the reversal of renal damage (Shuvy et al, 2011). In the present study, in DOCA rats with established renal injury, withdrawal of The Effect of CS-3150 on Renal Injury in DOCA Rats DOCA administration itself reversed renal injury.…”
Section: Induction Of Urinary Nasupporting
confidence: 47%
“…In another report, it has been shown that, in an adenine-loaded rat, which is widely used as a model for renal failure, cessation of the adenine diet led to the reversal of renal damage (Shuvy et al, 2011). In the present study, in DOCA rats with established renal injury, withdrawal of The Effect of CS-3150 on Renal Injury in DOCA Rats DOCA administration itself reversed renal injury.…”
Section: Induction Of Urinary Nasupporting
confidence: 47%
“…The renal toxicity of orally absorbed adenine is due to the formation of crystals that damage the nephrons. Indeed, adenine is metabolized to 2,8-dihydroxyadenine, which precipitates and forms tubular crystals that damage the renal tubules [11]. It is well known that 2,8-dihydroxyadenine exhibits a pH-dependent solubility in aqueous medium [35].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with adenine in the diet induces kidney fibrosis, increased blood urea nitrogen and plasma creatinine [8] associated with an enhanced oxidative stress [10]. Adenine is metabolized to 2,8-dihydroxyadenine, which precipitates and forms tubular crystals that damage the kidney tissues [11]. Adenine can also be metabolized by xanthine oxidase into uric acid that can also precipitate in renal tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Adenine causes crystal precipitates in renal tubules and forms 2,8-dihydroxyadenine aggregates. Adenine alone causes renal failure due to interstitial nephritis (32). Clinically, chronic long-term RF in patients results in abnormal phosphate metabolism.…”
Section: Animal Modelmentioning
confidence: 99%